The interaction between iNKT cells and B cells. Issue 3 (27th July 2021) - Zhu, Tong; Wang, Rongli; Miller, Heather; Westerberg, Lisa S; Yang, Lu; Guan, Fei; Lee, Pamela; Gong, Quan; Chen, Yan; Liu, Chaohong
Abstract: Invariant natural killer T cells (iNKTs) bridge the innate immunity with the adaptive immunity and their interaction with B cells has been extensively studied. Here, we give a complete overview of these two cells, from their mechanism of interaction to clinical prospects and existing problems. In our introduction, we describe the relationship between iNKTs and B cells and explore the current research hotspots and future directions. We begin with how B cells interact and benefit from the innate and adaptive help of iNKTs. Next, we describe the multiple roles of these cells in infections, autoimmunity, and cancers. Lastly, we look into the potential immunotherapies that can be based on iNKTs and the possible treatments for infectious, autoimmune, and other diseases. Graphical Abstract: Reviews the interaction between invariant natural killer T cells (iNKTs) and B cells and their impact on the treatment of infections, autoimmune diseases, cancers, and other diseases.